2021
DOI: 10.1021/acs.inorgchem.1c00908
|View full text |Cite
|
Sign up to set email alerts
|

Similar, Yet Different: Long-Range Metal–Metal Coupling and Electron-Transfer Processes in Metal-Free 5,10,15,20-Tetra(ruthenocenyl)porphyrin

Abstract: The electronic structure, redox properties, and long-range metal–metal coupling in metal-free 5,10,15,20-tetra­(ruthenocenyl)­porphyrin (H2TRcP) were probed by spectroscopic (NMR, UV–vis, magnetic circular dichroism (MCD), and atmospheric pressure chemical ionization (APCI)), electrochemical (cyclic voltammetry, CV, and differential pulse voltammetry, DPV), spectroelectrochemical, and chemical oxidation methods, as well as theoretical (density functional theory, DFT, and time-dependent DFT, TDDFT) approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…a nm-order highly delocalized system (>1 nm) (Figure d). Furthermore, modulation of the frontier orbital energies could be achieved by the choice of the metal centers embedded in the porphyrins. In this study, we have found that the combination of the metal acetylide MV systems and the metalloporphyrins leads to highly delocalized and stable MV systems as well as wide variation of their redox and charge-delocalized behavior. This reflects that the Zn and Ni centers embedded in the porphyrin BL* can also act as efficient modulators for the properties of the dinuclear organometallic wire. …”
Section: Introductionmentioning
confidence: 82%
“…a nm-order highly delocalized system (>1 nm) (Figure d). Furthermore, modulation of the frontier orbital energies could be achieved by the choice of the metal centers embedded in the porphyrins. In this study, we have found that the combination of the metal acetylide MV systems and the metalloporphyrins leads to highly delocalized and stable MV systems as well as wide variation of their redox and charge-delocalized behavior. This reflects that the Zn and Ni centers embedded in the porphyrin BL* can also act as efficient modulators for the properties of the dinuclear organometallic wire. …”
Section: Introductionmentioning
confidence: 82%
“…[43][44][45][46][47][48][49] Z. Zhao et al [50] used 1,1'bis(sulfonate)-ferrocene dianion disodium salt pared with the anthraquinone-2,7-disulfonic acid disodium salt; on the other hand, ferrocene decomposed under the acidic conditions used to stabilize the anthraquinone. [42] Considering our expertise in synthesis and applications of electro-active molecules, in particular metallocenes, [51][52][53][54] we synthesized in this work the 1,1'-bis(sulfonate)-ferrocene dianion disodium salt (DSÀ Fc) and two viologen-derivatives, as catholyte and anolyte, respectively, to produce a sustainable neutral-pH AORFB. The performances of the synthesized electrolytes were evaluated in terms of solubility, degradation capacity, retention, and electrical power generation.…”
Section: Introductionmentioning
confidence: 99%